Causes and consequences of the November 2014 torrential rains in the center & south of Morocco - Roman, Abdellatif; Ait Hssaine, Ali (International Journal of Environment, 2016)
In November 2014, the central and southern Morocco have experienced extreme rainfall reached 287 mm and exceeded 240 mm on the last ten days of that same month .In Agadir city the annual average precipitations is 236 mm. Through reading and analysis of a long chain of Agadir station climate data (100 years), it becomes clear that the exceptional rainfall, which resulted in catastrophic damage with colossal human as well as material losses, is by no means an isolated case. In fact, the region had experienced similar or greater amounts of rainfall before. If Agadir was not significantly damaged by the floods on 28 November 2014, compared to the nearby towns such as Ait Melloul, Tiznit and Sidi Ifni, it is because of the preventive measures taken to protect the city against such hazards, especially after the floods that the city of Agadir witnessed in December 2010. In this respect, we should especially mention the planning of drainage basins facing the city by building hilly dams and water disposal canals. International Journal of Environment Vol.5(3) 2016, pp.11-30